Development of a data encryption algorithm to enhance security in D2D communications by secure key exchange - Asaad, Essam Mohammad; Assalem, Abdulkarim (Journal of engineering sciences and information technology, 2023)
D2D (Device to Device) technology enables direct communication between devices and allows devices to act as a relay. It is one of the promising technologies, as it provides broader coverage and ensures an increase in cell capacity by increasing the capacity of users, as it allows devices to operate as eNB (eNodeB) or a small base station to form a small network in infrastructure or non-infrastructure mode, and these networks can be exposed to intrusions and threats Many of them: denial-of-service attacks, man-in-the-middle attacks, side channel attacks, and others. In this research, the focus is on the need to protect data, whether from hacking or copying, and thus accessing its contents and influencing the information exchange parties, and one of the most important methods of protection is information encryption. The importance of the research lies in the fact that it provides security protection for the D2D device-to-device communication system, by developing the key exchange protocol in the discovery stage based on the Diffi-Hellman key exchange algorithm, as well as proposing an encryption algorithm for the D2D communication technology based on the Logistic Map functions to secure the mixing process. Which is considered a first encryption stage because it depends on private keys in addition to balanced mixing equations for BBM blocks. Thus, the research aims to build an encryption system for D2D communication technology.